Labour, training and publication reciprocity between Library and Information Science and Social Communication - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2018)
This is a brief review of the relationship between Library and Information Science (LIS), Social Communication Sciences, and their journals in order to assess the validity of collaborative spaces. Professional profiles are analyzed that link the common competencies of both sectors. Then, we consider whether or not the necessary training to achieve these professional competencies is being supported in hybrid university programs. To conclude, the contributions of each sector in the scientific journals published by the reciprocal sector are considered, in particular those corresponding to ID. It is concluded that professional exchanges are more intense than university training and scholarly production, although there have been rapid and recent changes in publishing behavior.